Interstitial annelids from the Caribbean Coast of Colombia - Lagos, Ana Milena; Leon, M. Victoria; Quiroga, Sigmer Y.; Martínez, Alejandro (Revista de Biología Tropical, 2018)
A total of 298 species of polychaetes have been recorded from Colombia. However, only the family Protodrilidae has been reported from the marine interstitial realm. We here aim at identifying the interstitial annelids inhabiting the sandy beaches in Santa Marta region to the most accurate taxonomic level based on light microscopy examinations. Our samples, collected from the intertidal zone at three touristic beaches in the department of Magdalena (Santa Marta Bay, Rodadero Bay, and Taganga Bay), yielded a total of 83 specimens, which we assigned to five families, ten genera and nine species. From those, two families, eight genera, and the species Hesionides gohari, Neogyptis mediterranea, Neopetitia amphophthalma, Westheidesyllis gesae, and Syllis beneliahuae represent new records for the Colombian fauna. This survey should be considered as a first step towards a complete knowledge of the Colombian diversity of interstitial annelids, and our results significantly contribute to fill the gap of our current knowledge, suggesting a high diversity of species comparable to this in better-known areas of the Caribbean and the Atlantic coasts of Brazil. A brief diagnosis, comments on distribution and ecology, and remarks are provided for each record, in order to facilitate the re-identification of the species. Rev. Biol. Trop. 66(2): 658-673. Epub 2018 June 01.